Empty promises: The European Union is failing to protect dolphins and porpoises from fisheries by‐catch. Issue 4 (5th May 2021) - Rogan, Emer; Read, Andrew J; Berggren, Per
Abstract: By‐catch is the primary global conservation threat to populations of dolphins and porpoises. Despite protection for these protected species under its Habitats Directive, the European Union (EU) has failed to adequately assess and, where necessary, mitigate the by‐catch of small cetaceans. Management authority is diffuse, and the EU has no over‐arching, quantitative conservation objectives. To address this, we recommend that the EU adopt a comprehensive plan to conserve dolphins and porpoises in European waters. This plan should include regular formal assessments of small cetacean populations, including establishment of quantitative management objectives, generation of estimates of abundance and by‐catch mortality, and agreement on biological reference points that will guide management actions to ensure that by‐catch does not exceed sustainable levels.